2017
DOI: 10.1142/s0129065717500071
|View full text |Cite
|
Sign up to set email alerts
|

On the Methodological Implications of Extracting Muscle Synergies from Human Locomotion

Abstract: We investigated the influence of three different high-pass (HP) and low-pass (LP) filtering conditions and a Gaussian (GNMF) and inverse-Gaussian (IGNMF) non-negative matrix factorization algorithm on the extraction of muscle synergies from myoelectric signals during human walking and running. To evaluate the effects of signal recording and processing on the outcomes, we analyzed the intraday and interday computation reliability. Results show that the IGNMF achieved a significantly higher reconstruction qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
192
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(199 citation statements)
references
References 48 publications
7
192
0
Order By: Relevance
“…using the classical Gaussian NMF algorithm (Lee & Seung, ; Santuz et al . , , b ). The code is available at Zenodo (https://doi.org/10.5281/zenodo.2588332), together with some example data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…using the classical Gaussian NMF algorithm (Lee & Seung, ; Santuz et al . , , b ). The code is available at Zenodo (https://doi.org/10.5281/zenodo.2588332), together with some example data.…”
Section: Methodsmentioning
confidence: 99%
“…; Santuz et al . ) matrix H contained the time‐dependent coefficients of the factorization with dimensions r × n , where the number of rows r represents the minimum number of synergies necessary to satisfactorily reconstruct the original set of signals V . The motor modules (Gizzi et al .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…stance and swing phase) were obtained from the pressure plate. The touchdown and toe-off were determined from the ground reaction forces using a validated custom post-processing algorithm (Santuz et al, 2017), where the touchdown was identified as the first non-zero pressure matrix after the last toe-off. In addition to the contact times, the pressure data were used to quantify step lengths, cadence, vertical ground reaction forces (VGRFs) and total impulse of the stance phase for the gait cycles.…”
Section: Data Processingmentioning
confidence: 99%